Mekanisme penguatkuasaan halal premis makanan: Kajian di Kedah dan Pulau Pinang - Nor Aina Mardhiah, Nazim (2022)
The halal food industry in Malaysia is growing in line with the increasing awareness among consumers on halal food. Although the laws and regulations related to halal implementation in Malaysia have a good legal basis, there are problems regarding halal enforcement in Kedah and Penang. There are still food premise operators who display and abuse halal certification at food premises in these two states. This causes the enforcement of halal by halal enforcers to be questioned by various parties. Thus, this study aims to identify the laws and regulations related to halal enforcement on food premises, study the halal enforcement mechanism on food premises in Kedah and Penang and explore the views of food premise operators on halal enforcement mechanisms. To achieve all these objectives, this study used a qualitative approach in collecting data. This study used a content analysis method on documents and semistructured interviews with enforcers from the State Islamic Religious Department (JAIN), Ministry of Domestic Trade and Consumer Affairs (KPDNHEP) and the Municipal Council. Interviews were also conducted with food premise operators in Kedah and Penang who have Malaysian Halal Certification (MHC). Data collected was analysed using inductive analysis and Atlas Ti version 8 software. The findings show that the halal enforcement on food premises by JAKIM, JAIN and KPDNHEP have been conducted comprehensively since the existing jurisdictional provisions include halal marking, halal definition, and certification fees. In addition, the study found that the enforcers abide diligently to Standard Operating Procedures enforcement. The implications of the findings suggest that policies and regulations on Halal food should be clear and made available to improve Halal enforcement mechanisms and to assist food premise operators understand the enforcement requirements in Kedah and Pulau Pinang.